Elevated Plasma Growth and Differentiation Factor 15 Predicts Incident Anemia in Older Adults Aged 60 Years and Older - Yamaguchi, Yuko; Zampino, Marta; Tanaka, Toshiko; Bandinelli, Stefania; Osawa, Yusuke; Ferrucci, Luigi; Semba, Richard D (The journals of gerontology. Series A, Biological sciences and medical sciences, 2021)
Anemia is common in older adults and associated with greater morbidity and mortality. The causes of anemia in older adults have not been completely characterized. Although elevated circulating growth and differentiation factor 15 (GDF-15) has been associated with anemia in older adults, it is not known whether elevated GDF-15 predicts the development of anemia. We examined the relationship between plasma GDF-15 concentrations at baseline in 708 nonanemic adults, aged 60 years and older, with incident anemia during 15 years of follow-up among participants in the Invecchiare in Chianti (InCHIANTI) Study. During follow-up, 179 (25.3%) participants developed anemia. The proportion of participants who developed anemia from the lowest to highest quartile of plasma GDF-15 was 12.9%, 20.1%, 21.2%, and 45.8%, respectively. Adults in the highest quartile of plasma GDF-15 had an increased the risk of developing anemia (hazards ratio 1.15, 95% confidence interval 1.09, 1.21, p < .0001) compared to those in the lower 3 quartiles in a multivariable Cox proportional hazards model adjusting for age, sex, serum iron, soluble transferrin receptor, ferritin, vitamin B12, congestive heart failure, diabetes mellitus, and cancer. Circulating GDF-15 is an independent predictor for the development of anemia in older adults.